The Impact of Working Memory Training on Children's Cognitive and Noncognitive Skills - Eva M. Berger; Ernst Fehr; Henning Hermes; Daniel Schunk; Kirsten Winkel (Center for Economic Studies and ifo Institute (CESifo), 2024)
Working memory capacity is a key component of executive functioning and is thought to play an important role for a wide range of cognitive and noncognitive skills such as fluid intelligence, math, reading, the inhibition of pre-potent impulses or more general self-regulation abilities. Because these abilities substantially affect individuals' life trajectories in terms of health, education, and earnings, the question of whether working memory (WM) training can improve them is of considerable importance. However, whether WM training leads to spillover effects on these other skills is contested. Here, we examine the causal impact of WM training embedded in regular school teaching by a randomized educational intervention involving a sample of 6–7 years old first graders. We find substantial immediate and lasting gains in working memory capacity. In addition, we document positive spillover effects on geometry, Raven's fluid IQ measure, and the ability to inhibit pre-potent impulses. Moreover, these spillover effects emerge over time and only become fully visible after 12–13 months. Finally, we document that three years after the intervention the children who received training have a roughly 16 percentage points higher probability of entering the academic track in secondary school.
Keywords: 330